Gelombang Baru Studi Islam dan Masyarakat Muslim PascaOrientalisme - Muhammad Rofiq (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
This article underlines some misunder- standing in the Muslim communities concerning three concepts: orientalism, evangelism and imperialism. In the writer’s view point, orientalism has often been seen in it’s a pejorative and simplified meaning. Therefore the writer attempts to describe Western scholars’ responses to this understanding, and tries to explain some requirements that have been formulated by modern scholars, either Muslim or non-Muslim, regarding ap- proaches in the study of Islam in the framework of religious studies. The writer also argues to what extent that contem- porary Islamic studies (dirâsah islâmiyyah mu’âshirah) is supposed to synthesized between classical Islamic studies and western intellectual history in the study of Islam in the modern world.